EMPLOYING CONTEMPORARY TECHNOLOGIES FOR TEACHING RUSSIAN LANGUAGE AT A MEDICAL UNIVERSITY: EVALUATING THE EFFICACY OF DIGITAL TOOLS AND ONLINE PLATFORMS - Khamraeva Mavlyuda Juraevna (Bright Mind Publishing, 2025)
The presented article examines the application of contemporary digital technologies in the instruction of the Russian language at a medical university. It analyzes key digital resources and online platforms that enhance the educational process's effectiveness, including interactive applications, electronic textbooks, learning management systems (LMS), and specialized language training tools. The study places significant emphasis on evaluating the effectiveness of these resources through pedagogical and linguodidactic criteria, as well as their influence on the development of language competence tailored to professional needs among medical students. The findings of the research lead to the formulation of methodological recommendations for the incorporation of modern technologies into the educational framework, alongside examples demonstrating their successful implementation in teaching practices.
Keywords: Teaching Russian, medical university, digital technologies in education, distance learning, online education, electronic textbooks, effectiveness of online learning, interactive simulators, communication skills of a doctor, online platforms for learning, digital educational resources (DER), student achievements